1997
DOI: 10.1172/jci119713
|View full text |Cite
|
Sign up to set email alerts
|

Oral magnesium supplements reduce erythrocyte dehydration in patients with sickle cell disease.

Abstract: Intracellular polymerization and sickling depend markedly on the cellular concentration of sickle hemoglobin (Hb S). A possible therapeutic strategy for sickle cell disease is based on reducing the cellular concentration of Hb S through prevention of erythrocyte dehydration. The K-Cl cotransporter is a major determinant of sickle cell dehydration and is inhibited by increasing erythrocyte Mg content.We studied 10 patients with sickle cell disease before treatment and after 2 and 4 wk of treatment with oral Mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(90 citation statements)
references
References 38 publications
3
84
1
2
Order By: Relevance
“…Oral administration of clotrimazole to sickle cell patients, 35 as well as to transgenic sickle cell mice, 36 reduced the number of dense sickle cells in vivo. Following a suggestion first made by Bookchin et al, 37 De Franceschi et al 38,39 used oral Mg ϩϩ to increase cellular Mg ϩϩ , thereby inhibiting the KCl cotransporter, thought to be an important mediator of cation loss in sickle reticulocytes. 4,11 Mg ϩϩ supplementation reduced in vivo SS RBC dehydration in both mice and humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral administration of clotrimazole to sickle cell patients, 35 as well as to transgenic sickle cell mice, 36 reduced the number of dense sickle cells in vivo. Following a suggestion first made by Bookchin et al, 37 De Franceschi et al 38,39 used oral Mg ϩϩ to increase cellular Mg ϩϩ , thereby inhibiting the KCl cotransporter, thought to be an important mediator of cation loss in sickle reticulocytes. 4,11 Mg ϩϩ supplementation reduced in vivo SS RBC dehydration in both mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…4,11 Mg ϩϩ supplementation reduced in vivo SS RBC dehydration in both mice and humans. 38,39 In combination with other transport inhibitors, the inhibitory activity of dipyridamole against the sickling-induced transport pathway may prove useful in achieving inhibition of sickle cell dehydration in vivo with low levels of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The inactive human eAE1 mutant R760P (Band 3 Prague I), a cause of autosomal dominant hereditary spherocytosis, does not appear at the surface of the red blood cell or of the Xenopus oocyte and does not display a dominant negative anion exchanger phenotype (22). Similarly, AE1 Prague does not suppress mKCC1-mediated 86 Rb ϩ influx activity even when co-expressed at a 3-fold cRNA excess.…”
Section: Rbmentioning
confidence: 99%
“…Although high potency inhibitors of the IK1 erythroid KCa channel are available, clinically tolerated (21), and in continued development, high potency inhibitors of K-Cl cotransport have not been identified. KCC inhibitors could serve as an adjunct treatment of sickle cell disease, as shown to date with clinical trials of oral magnesium supple-mentation (22). Such specific KCC inhibitors would also provide a useful experimental tool to test the role of K-Cl cotransport in cell function.…”
mentioning
confidence: 99%
“…Orphan drugs for sickle vaso-occlusion with fluids and desmopressin proved too difficult to control, 85 but encouraging pilot studies with magnesium 86 and with clotrimazole 87 suggested that inhibition of the calcium activated potassium channel (Gardos channel) could be effective in increasing erythrocyte volume and reducing sickling. Senicapoc, a novel Gardos channel inhibitor, increased hemoglobin concentration with a concomitant decrease in total reticulocyte number and various markers of erythrocyte destruction in a Phase II study, 88 but a subsequent Phase III study was stopped early by its data safety monitoring board (DSMB) due to a lack of efficacy when it determined that despite improvements in anemia and hemolysis, there was no significant improvement in the rate of sickle cell painful episodes.…”
mentioning
confidence: 99%